Influence of vaccination against infectious diseases on the carbon footprint of fattening pigs: a systematic review - Gickel, Julia; Hartung, Clara Berenike; Abd El-Wahab, Amr; Hankel, Julia; Visscher, Christian (Frontiers in Veterinary Science, 2024)
IntroductionIn all sectors of the economy, including livestock production, there is an increasing focus on sustainability criteria. The carbon footprint is therefore an important target value in pig production. The aim is to minimize this value. Infectious diseases may affect the performance negatively, potentially leading to a higher carbon footprint. Therefore, vaccinations may be a useful tool to ensure a high level of sustainability in pork production.Materials and methodsThe aim of this evaluation was to assess the impact of vaccinations against Porcine Circovirus Type 2 (PCV2), Mesomycoplasma hyopneumoniae (M. hyo), both PCV2 and M. hyo, and Lawsonia intracellularis (LI) in epidemic situations in Europe on performance parameters using results from former publications on these diseases. These parameters were then used to calculate the carbon footprint of the pigs using life cycle assessment (LCA). The data collection with PubMed was based on the PRISMA guidelines for systematic reviews and meta-analyses, from which, however, some deviations were made. In total, 14 trials on PCV2, 10 trials on M. hyo, 14 trials on M. hyo and PCV2, and 17 trials on LI fulfilled the criteria and were included in this evaluation. In general, review articles and studies published before 1990 were excluded as were studies with incomplete data concerning the performance parameters and studies from non-European countries if the published body weights, genetics used, or other details in the experimental setup suggested they were not comparable to European standards.ResultsThe mean carbon footprint was up to 12.1% (PCV2), 2.5% (M. hyo), 9.3% (PCV2 and M. hyo), or 3.5% (LI) lower following a vaccination.DiscussionThis evaluation clearly shows that healthy animals can achieve a reduced carbon footprint through better performance with lower resource consumption, which is extremely important for sustainable animal husbandry. The use of health preserving measures such as vaccination can be a useful and important tool for reaching this goal.